2019
DOI: 10.1177/0738894219855610
|View full text |Cite
|
Sign up to set email alerts
|

Near crises in world politics: A new dataset

Abstract: Crisis escalation to war is a subject of longstanding interest. Case studies, formal models and statistical analysis offer compelling explanations for why some crises escalate to war while others do not. Much less can be said in answer to the following question: where do crises come from in the first place? In this paper, we first introduce the concept of a near crisis following the approach taken over the course of more than four decades by the International Crisis Behavior (ICB) Project. A near crisis is jus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…It was more than three decades ago when Leng (1983, 415), in one of the pioneering studies on recurrent crises, suggested that “we cannot entirely rule out the possibility that some of the bargaining that we observed [during international crises] may be caused by events occurring between the crises.” And yet, while different approaches in the conflict literature agree that international conflicts consist of interlinked phases, the intervals between recurrent confrontations are usually set aside in favor of studying more acute conflict situations. This study challenges such practice and joins a few recent efforts that call greater attention to various segments of a conflict process (Diehl, 2006; Iakhnis and James, 2019; Senese and Quackenbush, 2003). We still know relatively little about respite periods between recurrent confrontations, and even less so about the role they play in conflict escalation.…”
Section: Discussionmentioning
confidence: 89%
“…It was more than three decades ago when Leng (1983, 415), in one of the pioneering studies on recurrent crises, suggested that “we cannot entirely rule out the possibility that some of the bargaining that we observed [during international crises] may be caused by events occurring between the crises.” And yet, while different approaches in the conflict literature agree that international conflicts consist of interlinked phases, the intervals between recurrent confrontations are usually set aside in favor of studying more acute conflict situations. This study challenges such practice and joins a few recent efforts that call greater attention to various segments of a conflict process (Diehl, 2006; Iakhnis and James, 2019; Senese and Quackenbush, 2003). We still know relatively little about respite periods between recurrent confrontations, and even less so about the role they play in conflict escalation.…”
Section: Discussionmentioning
confidence: 89%
“…ICB defines a crisis as meeting three conditions: (1) an actor perceives a threat to one of more of its core values, (2) the actor has a finite time horizon for responding to the perceived threat, and (3) the probability of military hostility has increased (Brecher and Wilkenfeld, 1982). Crises are a significant focus of detailed single case studies and case comparisons because they provide an opportunity to examine behaviors in international relations short of, or at least prior to, full conflict (Holsti, 1965;Paige, 1968;Allison and Zelikow, 1971;Brecher and Wilkenfeld, 1982;Gavin, 2014;Iakhnis and James, 2019). The corpus is also unique in that it was designed to be used in a downstream quantitative coding project, meaning each narrative was written by a small number of scholars using a uniform coding scheme where things like word choice, writing style, and level of specificity were done deliberately and consistently (Hewitt, 2001).…”
Section: Corpusmentioning
confidence: 99%
“…We develop a large, flexible ontology of international events with the help of both human coders and natural language processing. We apply it sentence-by-sentence to an unusually high-quality corpus of historical narratives of international crises (Brecher 1999;Brecher, James, and Wilkenfeld 2000;Wilkenfeld and Brecher 2000;James 2019;Iakhnis and James 2019). The result is a new lower bound estimate of how much actually happens between states during pivotal historical episodes.…”
Section: Introductionmentioning
confidence: 99%